Selección de modelos termodinámicos electrolíticos y su aplicación para sistemas de mezclas de solventes y sales inorgánicas disueltas (2018)
In this paper is presented a qualitative description of pseudobinary composition curves, a thermodynamic topological tool used to describe the phase equilibria variation degree in a binary system when is added a third compound, study case is ethanol-water-inorganic salt (calcium chloride, potassium iodide and sodium chloride) ternary system. Ionic substances usage requires employing an electrolytic thermodynamic model that was selected with a decision tree. The commercial simulator Aspen Plus 8.6® and the software Microsoft 2013® was used to perform mathematical development.